Improving fruit traits of 'Braeburn' apples in low-altitude regions: The impact of foliar spray and rootstock interactions - Leili Habibzadeh; Mahdi Alizadeh; Mohammad Mehdi Sharifani (Journal of Horticulture and Postharvest Research)
Purpose: The ‘Braeburn’ apple, cultivated in Mashhad, Iran, has poor red coloration that affecting its marketability. This research studied the effects of mono-potassium phosphate (MKP) and calcium prohexadione (ProCa) on red pigment development and biochemical traits, as well as interactions with two rootstocks used for grafting. Research method: The experimental treatments included four concentrations of MKP (0, 0.1, 1.0, and 2.0 g/L) sprayed in three periods: 20 days after petal fall, 45 and 30 days before commercial fruit harvest. Furthermore, ProCa was also applied in four concentrations (0, 125, 250, and 500 mg/L), one month before harvest (three times with 10-day intervals). Findings: The results showed that M.9 rootstock led to larger fruit diameters compared to MM.111, but overall physical traits remained unchanged. Chemical applications significantly affected fruit diameter and firmness, with ProCa treatments (250 and 500 mg/L) yielding the highest firmness levels. Rootstock type influenced total acidity (TA), total soluble solids (TSS), flavor index, and vitamin C content. M.9 rootstock combined with MKP spray resulted in the best TA, TSS, and flavor index. However, higher ProCa concentrations negatively impacted color development and anthocyanin levels. Thus, cultivating red apple cultivars in low-altitude regions like Mashhad is not recommended due to environmental factors affecting pigmentation. Research limitations: There was no apple orchard of the same variety located in a higher altitude within the same region for a comparative analysis. Originality/Value: The article clearly emphasizes that the orchard establishment of the ‘Braeburn’ apple is not technically authorized for low altitude places (lower than 1000 m).